Global research trends on gut microbiota and metabolic dysfunction-associated steatohepatitis: Insights from bibliometric and scientometric analysis - Alam, Naqash; Jia, Linying; Cheng, Ao; Ren, Honghao; Fu, Yu; Ding, Xinhua; Haq, Ihtisham Ul; Liu, Enqi (Frontiers in Pharmacology, 2024)
Background: Metabolic dysfunction-associated steatohepatitis (MASH) is an inflammatory subtype of metabolic dysfunction-associated steatotic liver disease (MASLD) has recently been proposed as a replacement term for NAFLD, a common, multifactorial and poorly understood liver disease whose incidence is increasing worldwide. In recent years, there has been increasing scientific interest in exploring the relationship between gut microbiota and MASH. To learn more about the gut microbiota in MASH, this study aims to provide a comprehensive analysis of the knowledge structure and research hotspots from a bibliometric perspective.We searched the Web of Science Core Collection for articles and reviews that covered the connections between gut microbiota and MASH over the last decade. The Online Analysis Platforms, VOSviewer, CiteSpace, the R tool "bibliometrix" were used to analyzed existing publications trends and hotspots.Results: A total of 4,069 documents related to the interaction between gut microbiota and MASH were retrieved from 2014 to 2023. The number of annual publications increased significantly over the last decade, particularly in the United States and China. The University of California-San Diego was the most productive institution, while researcher Rohit Loomba published the most papers in the field. Younossi ZM was ranked as the first co-cited author and largest contributor of highly cited articles in the field. Gastroenterology and hepatology were the most common specialty category. The most cited journal in the last decade was Hepatology. The Keyword Bursts analysis highlighted the importance of studying the association between gut microbiota and MASH, as well as related factors such as metabolic syndrome, insulin resistance, endotoxemia and overgrowth of gut bacteria. Keyword clusters with co-citation were used to illustrate important topics including intestinal permeability, insulin sensitivity and liver immunology. The most common keywords include insulin resistance, obesity, dysbiosis, inflammation and oxidative stress, which are current hotspots.Our analysis highlights key aspects of this field and emphasizes multiorgan crosstalk in MASLD/MASH pathogenesis. In particular, the central role of the gut-liver axis and the significant influence of gut microbiota dysbiosis on disease progression are highlighted. Furthermore, our results highlight the transformative potential of microbiota-specific therapies and cover the way for innovative healthcare and pharmaceutical strategies.